Update on the Standard Template to Collect Data on Government Revenues from Natural Resources. (Policy Papers; Policy Paper ;, 2017)
The paper presents an update on the status of the standard template to collect data on government revenues from natural resources, originally presented to the Executive Board in January 2014. The paper discusses: (i) the field-testing of the standard template in six countries, which confirmed the feasibility of applying it more broadly; (ii) the final version of the template based on outcomes of consultation with the international community and the field-testing visits; and (iii) the adoption of the template by the Extractive Industries Transparency Initiative (EITI) International Secretariat as a mandatory reporting requirement for its member countries. The standard template serves as a companion to the Guide to Analyze Natural Resources in the National Accounts. The standard template was developed to support fiscal policy formulation and analysis in resource-rich economies, which constitute about one third of the Fund's membership. The standard template is based on the revenue classification of the Government Finance Statistics Manual 2014, thereby facilitating the collection of resource revenue data in methodologically sound, analytically relevant, and cross-country comparable format.